Advances in taxation. Vol. 21 - Stock, Toby, 1961- (Advances in taxation, 2014)
Advances in taxation publishes relevant, quality manuscripts addressing the issues of federal, state, local and international taxation including tax compliance, tax planning, and tax policy issues among others. The series uses a wide variety of research methods, including analytical modelling, archival, experimental, survey, descriptive, and legal approaches to address the problems and issues associated with taxation. Volume 21 of Advances in Taxation continues this broad approach to taxation, looking at taxpayer compliance, state tax issues and tax policy decisions, amongst others.